2001
DOI: 10.1074/jbc.m108136200
|View full text |Cite
|
Sign up to set email alerts
|

Folded Monomer of HIV-1 Protease

Abstract: The mature human immunodeficiency virus type 1 protease rapidly folds into an enzymatically active stable dimer, exhibiting an intricate interplay between structure formation and dimerization. We now show by NMR and sedimentation equilibrium studies that a mutant protease containing the R87K substitution (PR R87K ) within the highly conserved Gly 86 -Arg 87 -Asn 88 sequence forms a monomer with a fold similar to a single subunit of the dimer. However, binding of the inhibitor DMP323 to PR R87K produces a stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
133
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(143 citation statements)
references
References 32 publications
9
133
1
Order By: Relevance
“…The 1 H-15 N HSQC spectrum of PR T26A is similar to those of PR-(1-95) and PR R87K monomers (Fig. 3B) (16), demonstrating that PR T26A is also a folded monomer. 15 N NMR relaxation measurements on PR R87K in the absence of inhibitor DMP323 revealed significant motions on the subnanosecond time scale for the N-and C-terminal residues 2-10 and 93-99 unique to the monomer (16).…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…The 1 H-15 N HSQC spectrum of PR T26A is similar to those of PR-(1-95) and PR R87K monomers (Fig. 3B) (16), demonstrating that PR T26A is also a folded monomer. 15 N NMR relaxation measurements on PR R87K in the absence of inhibitor DMP323 revealed significant motions on the subnanosecond time scale for the N-and C-terminal residues 2-10 and 93-99 unique to the monomer (16).…”
Section: Resultsmentioning
confidence: 53%
“…Disrupting the D29/R87 Interaction Destabilizes Dimer Formation-We previously demonstrated that a protease construct bearing the conservative mutation R87K does not exhibit dimer formation, even at concentrations up to ϳ1 mM (16). This suggested that an interaction involving the side chain of Arg 87 , most likely the one between Arg 87 and Asp 29 , stabilized the dimer, possibly by anchoring the ␣-helix and thereby correctly positioning the two C-terminal strands of the ␤-sheet.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations